Application of unascertained measure model in reservoir potential evaluation of Nanpu H Fault Block - QU Lili, LI Minglin, WU Zhimin, ZHANG Lin, FENG Linping, DENG Liping (Youqicang pingjia yu kaifa)
How to accurately evaluate the current reservoir potential directly affects the potential tapping of remaining oil by water injection in complex fault block reservoirs during the middle and late stages of development. By the comprehensive analysis of static reservoir geological characteristics and dynamic development effects, the main control factors of residual oil distribution in complex fault block reservoirs are determined, and the reservoir potential is evaluated by the analytic hierarchy process combined with unascertained measure evaluation method based on unascertained mathematical theory and attribute measurement theory. An accurate unascertained measure function is established by building an evaluation index system, and by the confidence degree identification criteria to determine the evaluation space, the evaluation result of reservoir potential is finally obtained. The research results show that the reservoir potential is comprehensively evaluated by using the analytic hierarchy process and unascertained measurement, the evaluation system consisting of seven parameters is established and the unascertained measurement function is constructed. According to the reservoir potential, the reservoirs can be divided into four categories, of which category Ⅰ and category Ⅱ have good potential. The evaluation results are similar to the numerical simulation results, and the reliability of the evaluation results is verified by the on-site implementation.